THE RELATIONSHIP BETWEEN SOCIOECONOMIC STATUS AND THE INCIDENCE OF STUNTING IN NGALANG GUNUNGKIDUL - Fitriani, Fifin Dewi; Sunarsih, Tri (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Stunting is one of the nutritional status cases experienced by most toddlers worldwide. WHO 2020 revealed that Indonesia is the second country in Asia with the highest prevalence of 31.8% of stunting problems in toddlers. Several factors cause toddlers to experience stunting, including indirect factors, namely socioeconomic status. The socioeconomic status of the residents of Ngalang on the incidence of stunting toddlers aged 12-60 months was found to be 40 toddlers short and 6 toddlers very short. This study was conducted to determine the relationship between socioeconomic status and the incidence of stunting in Ngalang Gunungkidul. This type of quantitative research uses a cross-sectional design. Population 85 parents of toddlers 12-60 months with stunting conditions. The sample was obtained using the Solvin method: 46 parents of stunted toddlers who met the inclusion criteria. After the Spearmen rho test was obtained, many members in the family p=0.019; of many children of the family, p=0.010, the father's educational status is p=0.058, the mother's educational status is p=0.025, and the monthly income in the family p=0.023. There is Stunting is a prevalent nutritional issue among toddlers globally. The results showed a significant relationship between family size, number of children, mother's educational status, family income, and stunting in toddlers. However, no significant relationship was found between the father's educational status and stunting, suggesting the need for further research on the father's role. Preventative measures include participating in premarital classes and prioritizing a child's growth and development through proper nutrition, parenting, healthcare, and environmental sanitation.Keyword: Socioeconomics, Stunting, toddlers